2015
DOI: 10.1021/ma502281k
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Morphology, Modulus, and Conductivity in Polymer Electrolytes Prepared via Polymerization-Induced Phase Separation

Abstract: Polymer electrolytes are alternatives to liquid electrolytes traditionally used in electrochemical devices such as lithium-ion batteries and fuel cells. In particular, block polymer electrolytes are promising candidates because they self-assemble into well-defined microstructures, in which orthogonal properties can be integrated into a single material (e.g., high modulus in domain A, fast ion transport in domain B). However, the performance of block polymer electrolytes often falls short, due to the lack of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 60 publications
6
97
0
Order By: Relevance
“…Conductivity decreases with increasing N A : N B block ratios and polymer concentration but generally remains near neat [BMI][TFSI] ( σ gel / σ IL ∼ 0.2–0.8). Ion gels and related IL‐incorporating polymers provide extraordinary opportunities to specifically tailor materials for technological applications. Appreciating the connection between polymer architecture and properties may facilitate the development of designer materials with improved function.…”
Section: Discussionmentioning
confidence: 99%
“…Conductivity decreases with increasing N A : N B block ratios and polymer concentration but generally remains near neat [BMI][TFSI] ( σ gel / σ IL ∼ 0.2–0.8). Ion gels and related IL‐incorporating polymers provide extraordinary opportunities to specifically tailor materials for technological applications. Appreciating the connection between polymer architecture and properties may facilitate the development of designer materials with improved function.…”
Section: Discussionmentioning
confidence: 99%
“…This cross‐linked material exhibited high‐temperature stability and a bicontinuous morphology. Hillmyer and co‐workers extended this PIPS approach to generate nanostructured polymer electrolyte membranes through the integration of ionic liquid and Li‐salt as the liquid precursor, and these membranes showed high‐temperature stability, modulus, and ionic conductivity . Shirshova et al reported multifunctional, structural electrolytes using an epoxy resin (where epoxides have the ability to form bicontinuous structure via PIPS) and a liquid electrolyte comprising an ionic liquid (possessing high ionic conductivity and thermal stability) and a lithium salt.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] To date, a host of ingredients (metals, 8 oxides, 9,10 surfactants, 6 and polymers 3 ) and processing strategies (both kinetic 11,12 and thermodynamic 3,6 ) have been exploited to control the characteristic length scale and physical properties of such co-continuous structures. 3,4,12,[15][16][17][18][19][20][21] For example, recent work has shown that a kinetically controlled co-continuous structure with nanometer scale features can be trapped by in situ cross-linking through a process called polymerization-induced microphase separation. 13,14 A variety of approaches afford access to characteristic length scales in co-continuous polymeric systems that range from nanometers to millimeters.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are particularly attractive for this purpose. 12,20,22 In contrast, coarsening of a two-phase morphology generated by spinodal decomposition of polymer/solvent blends can lead to bicontinuous structures with micrometer, and even millimeter size domains. 3,4,12,[15][16][17][18][19][20][21] For example, recent work has shown that a kinetically controlled co-continuous structure with nanometer scale features can be trapped by in situ cross-linking through a process called polymerization-induced microphase separation.…”
Section: Introductionmentioning
confidence: 99%